Language of Science and Teaching Learning of Science A Constructivism Oriented Interface Overview - Parida, B.K.; Mohapatra, J. K. (JOURNAL OF INDIAN EDUCATION, 2015)
In view of the indifferent attitude of students, teachers as well as teacher educators associated with science education towards language and consequences thereof, the authors attempt to highlight various issues related to language of science and its practice in teaching learning situations. This is important because (i) language is an essential tool for knowledge acquisition in constructivist paradigm, and (ii) language deficiency acts as an impediment in the academic growth and career of an individual, apart from the fact that language is central to knowledge creation and dissemination.